Availability of Emergency Department Wait Times Information: A Patient-Centered Needs Assessment - Samantha Calder-Sprackman; Edmund S. H. Kwok; Renee Bradley; Jeffrey Landreville; Jeffrey J. Perry; Lisa A. Calder (Emergency Medicine International)
Introduction. Many Emergency Departments (ED) publish wait times; however, the patient perspective in what information is requested and the quantity of information to post is limited. Methods. We conducted a mixed-methods study at a tertiary care academic center. First, we conducted focus groups of 7 patients. We then generated themes following content analysis to create a patient survey. We administered in-person surveys to patients in ED waiting rooms at sites randomized for survey administration. We used preassigned shifts utilized for even patient perspective representation of the 24 hours-a-day/7 days-a-week service. We included waiting room patients over 18 years of age and excluded patients directly referred to a specialty service or who did not speak French or English. We analyzed survey data using descriptive statistics. Results. We identified nine dominant focus group themes: wait time definition, wait time notification, communication, education, patient expectations, utilization of the ED, patient behaviour, physical comfort, and patient empowerment. Of the 240 patient questionnaires administered, 81.3% of respondents wanted to know ED wait times before hospital arrival hospital and 90.8% wanted ED wait times posted in the waiting room. Website (46.7%) was the most popular choice for publishing wait times outside the ED. Within the ED, patients had no preference regarding display modality, if times were displayed (39.6%). Overall, 76.7% stated that their satisfaction with the ED would be improved if wait times were posted. Conclusion. ED patients strongly supported having access to wait time information. Patients believed having wait time information will have a positive impact on their overall ED satisfaction.